University Performance in the Era of Digital Transformation - Trisninawati, Trisninawati; Helmi, Sulaiman (Borong Newinera Publisher, 2024)
In today's rapidly developing digital era, Digital Transformation has become necessary for many institutions, including educational institutions such as universities. Digital Transformation refers to using information and communication technology to improve an organization's efficiency, quality and competitiveness. On the other hand, Brand Image is the public's perception of an institution or company, including universities. In a global context that is increasingly connected and changing rapidly, the role of Digital Transformation in higher education is increasingly becoming a main focus. This research is a type of research that uses a qualitative approach. What is meant by this type of research is in the form of a case study, which is social research which aims to interview and describe data found in the field. This research aims to find data about the problem being researched and the research result. This method will then be carried out to find out the problem that is the research theme, and the survey data will be subjected to a descriptive qualitative approach, which will explain and answer the problem formulation of this research. This research shows that the relationship between Digital Transformation and University Brand Image is very close and influences each other. Digital Transformation significantly impacts the image and reputation of a higher education institution. By effectively implementing information and communication technology, universities can improve operational efficiency, service quality, user experience, and stakeholder engagement. This directly strengthens the university's brand image as a modern, quality, innovative and solution-oriented institution.